ESTIMATING SOIL LOSS BY WATER EROSION (University of Thi-Qar Journal for Engineering Sciences, 2013)
The study is focused on the estimation of rate of soil erosion, using the Universal Soil Loss Equation(USLE), for the embankment of Al-Garma Bridge in Basrah, Iraq. The soil erosion is estimated for the zone of average slope in the study area. The factors considered are rainfall, intensity of rainfall, type of soil, slope length, slope steepness, land use classification, and the existing of soil conservation practices. Detailed analysis of soil samples were done to asses the texture, structure, permeability and organic matter content of the soil samples of the embankment of the Al-Garma Bridge. The average annual erosivity index is obtained as (124.99(MJ. mm/(ha.h))) and the annual average soil erosion rate is estimated as (61.5 t/ha/year).